Bilirubin Nanoparticles Reduce Diet-Induced Hepatic Steatosis, Improve Fat Utilization, and Increase Plasma β-Hydroxybutyrate - Hinds, Terry D.; Creeden, Justin F.; Gordon, Darren M.; Stec, Donald F.; Donald, Matthew C.; Stec, David E. (Frontiers in Pharmacology, 2020)
The inverse relationship of plasma bilirubin levels with liver fat accumulation has prompted the possibility of bilirubin as a therapeutic for non-alcoholic fatty liver disease (NAFLD). Here, we used diet-induced obese (DIO) mice with NAFLD treated with pegylated bilirubin (bilirubin nanoparticles) or vehicle control to determine the impact on hepatic lipid accumulation. The bilirubin nanoparticles significantly reduced hepatic fat, triglyceride accumulation, de novo lipogenesis, and serum levels of liver dysfunction marker aspartate transaminase (AST) and ApoB100 containing very-low-density lipoprotein (VLDL). The bilirubin nanoparticles improved liver function and activated the hepatic β-oxidation pathway by increasing PPARα and acyl-coenzyme A oxidase 1 (ACOX1). The bilirubin nanoparticles also significantly elevated plasma levels of the ketone β-hydroxybutyrate (BOHB) and lowered liver fat accumulation. This study demonstrates that bilirubin nanoparticles induce hepatic fat utilization, raise plasma ketones, and reduce hepatic steatosis, opening new therapeutic avenues for NAFLD.